PENGATURAN TANGGUNG JAWAB KURATOR TERHADAP PENGURUSAN DAN PEMBERESAN HARTA PAILIT DALAM KAITANNYA DENGAN HAK KREDITOR SEPARATIS - Dewi Tuti Muryati; Dhian Septiandani; Efy Yulistyowati (Universitas Semarang, 2017)
Bankrupt is a situation where the debtor is unable to make payments on his debts to one or more creditors. With the general confiscation against the bankruptcy estate, the management and settlement of property made by a debtor or a curator or Heritage Hall (BHP) under the supervision of the Supervisory Judge who appointed simultaneously by the Commercial Court at the time of the decision of a declaration of bankruptcy debtors. This is in accordance with the provisions of Article 69 paragraph (1) of Law No. 37 of 2004 which states that